Criar, empreender e inovar: um estudo sobre o DNA criativo israelense - Corbo, Yasmin Costa Dutra de Oliveira (2021)
The present work aims to identify the aspects of a culture focused on creativity present in the personal stories of the contemporary Israeli community, realizing the behavioral aspects related to culture, habits related to creativity and understanding the relationship between the aspects with the design culture, carried out through a exploratory qualitative research. The collective configuration of the Jewish community, as well as the contemporary configuration of Israel as a State and all the complexity of defining Israeli identity were addressed in the research. To this end, a theoretical bibliographic research stage and an identification stage were developed, which was divided between the development of a focus group and the collection of oral histories by three Israelis representing the areas of design / art, innovation and entrepreneurship, as a way to identify in their personal experiences the aspects noted in the theoretical stage